If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -2) = 15p + 60 Reorder the terms: 3(-2 + y) = 15p + 60 (-2 * 3 + y * 3) = 15p + 60 (-6 + 3y) = 15p + 60 Reorder the terms: -6 + 3y = 60 + 15p Solving -6 + 3y = 60 + 15p Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3y = 60 + 6 + 15p Combine like terms: -6 + 6 = 0 0 + 3y = 60 + 6 + 15p 3y = 60 + 6 + 15p Combine like terms: 60 + 6 = 66 3y = 66 + 15p Divide each side by '3'. y = 22 + 5p Simplifying y = 22 + 5p
| 2x-832x/9 | | (x+1)(x-3)(x-3+3i)(x-3-3i)=equation | | -log(x-5)+log(x+5)=2 | | 126=6x+1+5x+17 | | 12(n-4)-3n=p | | 5(2x+6)=-4(-5-2x)-3x | | 15x+6-4x+2=-48 | | B^2-8b-45=0 | | (2h^2+h-1)(h-5)= | | 10(x/10) | | 10(x-1)=5(2x-2) | | -7w-2(5-6w)= | | 0.75/50 | | 8x+3x=422 | | 4(5x+1)=-236 | | 16x+12=5x | | 3/4x2/5 | | 2(lw)=8 | | (x-2)(x+3)-14=0 | | -18(c-1)-18=p | | t^2(t^4-10t^2+9)=0 | | 2(3y-12)+4=-4 | | 5=-32+b | | Y=100-60 | | t/4-17=13 | | 7x+6=30-x | | 6y+3=3y+3 | | -7-4x=-6x-27 | | 4x+5-4x=6 | | 2x=-4-2y | | 15-6x/12=3/4 | | P(2)=4.05 |